MAQÂSHID SYARÎ'AH APPROACH ON THE EMPOWERMENT OF HUMAN RESOURCES IN MULYODADI VILLAGE BANTUL YOGYAKARTA - Syamsuri Syamsuri; Okta Yuripta Syafitri (State Islamic University North Sumatra, 2018)
Abstract: The process of community economic development by involving the community directly from planning, implementation to evaluation is a model of empowerment that raises human dignity on the real essence. The villagers is not only an object of development, but every individual is required to be involved in the whole process of empowerment. This article tries to analyze the inhibiting factors as well as solutions of empowerment program of Human Resources in Mulyodadi village. By using qualitative method and taking data through interview, observation, and documentation (triangulation). Finally this article found two factors inhibiting the empowerment of human resources that is internal and external aspects. However, these two factors can be solved with some solutions and approaches made by the government and the community.Abstrak: Pendekatan maqâshid syarî‘ah terhadap Penguatan Sumberdaya Manusia di Desa Mulyodadi Bantul Yogyakarta. Proses pembangunan ekonomi masyarakat dengan melibatkan masyarakat secara langsung mulai perencanaan, pelaksanaan hingga evaluasi merupakan model pemberdayaan yang memanusiakan manusia pada hakekat sebenarnya. Masyarakat desa tidak hanya menjadi objek pembangunan atau program yang bersifat top-down, melainkan setiap individu dituntut terlibat dalam seluruh proses pemberdayaan. Artikel ini mencoba menganalisis faktor penghambat sekaligus solusi program pemberdayan Sumber Daya Manusia di desa Mulyodadi. Dengan menggunakan metode kualitatif dan pengambilan data melalui wawancara, observasi, dan dokumentasi (triangulasi). Artikel ini menemukan bahwa terdapat dua faktor penghambat pemberdayaan SDM yaitu aspek internal dan eksternal. Akan tetapi kedua faktor tersebut mampu diselesaikan dengan beberapa solusi dan pendekatan yang dilakukan oleh pihak pemerintah maupun masyarakat.Keywords: maqâshid syarî‘ah, human resources, Bantul, economic development